Studi Kohabitasi antara Langur Borneo (Presbytis chrysomelas ssp. cruciger) dan Bekantan (Nasalis larvatus) di Taman Nasional Danau Sentarum - Santoso, Nyoto; Diva, Alfatheya Margwita; Fauziah, Natasya Nurul; Sutopo, Sutopo (Jurnal Ilmu Kehutanan, 2023)
The tricolour langur and proboscis monkey in Bukit Semujan cohabited and utilized the same resources. Cohabitation, mainly due to resource constraints, needed substantial attention to ensure the survival of these primates. This research aimed to map the utilization of canopy strata vertical forest structure and vegetation as food sources and identify the size and overlap of ecological niches for both primates. This research occurred in Danau Sentarurn National Park (DSNP) from July to December 2021. The data collection employed the ad libitum method. The results indicated that cohabitation occurred in the canopy strata vertical forest structure utilization, particularly stratum B and C, and was related to food availability for both primates. The Jaccard Index of the stratum utilization association was 0.6 for swamp forests and 0.8 for hillside forests, while the food plant association was 0.2. In addition, the ecological niche of the tricolour langur overlapped 48% against the proboscis monkey and 34% on the contrary. The tricolour langur's niche size (FT) was 0.32278 ≤ 0.5960 ≥ 0.81253, while the proboscis monkey was 0.20866 ≤ 0.52837 ≥ 0.78529 at 95% confidence interval.